PELUANG INTENSIFIKASI RUANG TUMBUH BAWAH TEGAKAN AGROFORESTRY TEGALAN MELALUI INTRODUKSI WIJEN (Sesamum indicum L.) DI PERBUKITAN MENOREH KULON PROGO - , Aditya Hani ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Efforts to increase the added value of the land can be done by planting species understory with a high commercial value. One type is the opportunity to develop sesame (Sesamum indicum L.). This study aims to: 1) determine morphological, physiological responses, productivity and quality of sesame (S.indicum L.) on three (3) levels of intensity of shade